THE EFFECT OF PHYTOMELIORANT CROPS ON THE ACCUMULATION OF SALT IN THE SOIL, NORMS FOR WASHING SOIL BRINE - Sh. M. Xamidova; U. A. Juraev; A. N. Sadullayev (Journals Park Publishing, 2022)
The article presents the results of scientific research work carried out to optimize the water and salt procedures of soils in the conditions of moderately saline soils in terms of alluvial, mechanical composition of the Bukhara region with the help of phytomeliorative measures, to economize river waters spent on irrigation and salt washing of agricultural crops
Keywords: Climate change; irrigation desiccation; water resources